Golf swing analysis by an inertia sensor and selecting optimum golf club - Naruo, T.; Kawashima, K.; Kimura, T.; Oota, Y.; Kanayama, T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this research is to build a system to analyse golf swing by using an inertia sensor and select the optimum specifications of a golf club for a golfer. As a result of analysing the relation between golf swing and the specifications of a golf club specializing in the mass characteristic, it became apparent that the specifications connected with the easiness of swing are; the moment of inertia and the length of equivalent simple pendulum of the golf club. The mass property to match each golfer can be specified if 15 parameters are obtained from the inertia sensor attached to the left back of the hand of a right-handed golfer.